(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2020)
In this paper we study a new dimension on warehouse with Artificial bee colony algorithm using genetic algorithm processes in Six Stages - 11 Member Supply Chain in inventory optimization to describe the certain and uncertain market demand which is based on supply reliability and to develop more realistic and more flexible models. The proposed study has a great potential to solve various practical tribulations related to the warehouse using genetic algorithm processes in Six Stages - 11 Member Supply Chain in inventory optimization. It provides a general review for the application of soft computing techniques like genetic algorithms for the improvement of effectiveness and efficiency for various aspect of warehouse with Artificial bee colony algorithm using genetic algorithm.